Vit Bubenik, Hellenistic and Roman Greece as a sociolinguistic area, Amsterdam-Philadelphia, Currents Issues in Linguistic Theory 57, John Benjamins Publishing Company, 1989, XV + 331 pp. ISBN 90-272-3551-1 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Vit Bubenik, Hellenistic and Roman Greece as a sociolinguistic area, Amsterdam-Philadelphia, Currents Issues in Linguistic Theory 57, John Benjamins Publishing Company, 1989, XV + 331 pp. ISBN 90-272-3551-1